2022
DOI: 10.3390/diagnostics12020399
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Magnetic Resonance in Myocarditis

Abstract: Myocarditis is an inflammatory disease of the myocardium, and its diagnosis remains challenging owing to a varying clinical presentation and broad spectrum of underlying aetiologies. In clinical practice, cardiovascular magnetic resonance has become an invaluable non-invasive imaging tool in the evaluation of patients with clinically suspected myocarditis, mainly thanks to its unique multiparametric tissue characterization ability. Although considered as useful, the method also has its limitations. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 126 publications
(221 reference statements)
1
32
0
2
Order By: Relevance
“…The AUCs of LGE and T 2 showed the best discrimination of both groups with an LGE extent > 2.8% of LV myocardial mass and T 2 > 51 ms. This might be explained by a decrease of inflammation from the acute to the subacute phase [ 42 ]. T 1 mapping has proven to be a sensitive marker for myocardial disease of different entities [ 33 , 43 ], but seems limited for discrimination of acute from chronic processes [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The AUCs of LGE and T 2 showed the best discrimination of both groups with an LGE extent > 2.8% of LV myocardial mass and T 2 > 51 ms. This might be explained by a decrease of inflammation from the acute to the subacute phase [ 42 ]. T 1 mapping has proven to be a sensitive marker for myocardial disease of different entities [ 33 , 43 ], but seems limited for discrimination of acute from chronic processes [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…CMR studies were performed using a 1.5-T magnetic resonance imaging scanner (Gyroscan Intera or Achieva; Philips Healthcare, Best, The Netherlands) with a cardiac-dedicated phased-array coil, under electrocardiogram gating, and breath-holding in line with standard recommendations [ 21 ]. LV volumes were obtained by manual tracing of the epicardial and endocardial contour in end-diastole in the short axis (SA) slices of the continuous SA stack, propagated through all phases using a semi-automated tracing algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…Ten minutes after an intravenous injection of 0.2 mmol/kg gadolinium, inverse recovery sequences were obtained to assess for the presence of gadolinium-enhancing lesions (LGE). The optimal inversion recovery time was defined as previously described [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The fumarate-to-malate hydration reaction is catalyzed by the intracellular enzyme fumarase as part of the tricarboxylic acid cycle. Animal studies have demonstrated that myocyte necrosis exposes the [1,[4][5][6][7][8][9][10][11][12][13] C 2 ] fumarate molecule to fumarase, leading to production of [1,[4][5][6][7][8][9][10][11][12][13] C 2 ]malate, which does not occur when cell membranes are intact. 101 Although yet to be translated to clinical use, hyperpolarized [1,4-13 C 2 ]fumarate holds promise as a biomarker of active necrosis in inflammatory heart diseases and could aid in detecting disease activity and evaluating response to treatment.…”
Section: Carbon ( 13 C) and Hyperpolarized Mrimentioning
confidence: 99%